Sinonasal adenocarcinoma: Population‐based analysis of demographic and socioeconomic disparities. Issue 10 (12th June 2021) - Low, Christopher M.; Balakrishnan, Karthik; Smith, Byron M.; Stokken, Janalee K.; O'Brien, Erin K.; Van Gompel, Jamie J.; Rowan, Nicholas R.; Choby, Garret
Abstract: Background: Sinonasal adenocarcinoma (SNAC) is a rare tumor. The impact of health disparities on survival, stage at presentation, and utilization of surgery is not well understood in patients with SNAC. Methods: The Surveillance, Epidemiology, and End Results database was queried for cases of SNAC from 1973 to 2015. Cases were analyzed to assess for disparities in presentation, treatment, and survival. Results: SNAC was identified in 630 patients. In a multivariate model of overall survival, an age increase of 10 years (Hazard Ratio (HR) = 1.37, p < 0.001), male sex (HR = 1.26, p = 0.045), and more recent decade of diagnosis (HR = 0.74, p < 0.001) were significantly related to time‐to‐death. There is a higher rate of SNAC‐related death in counties with more rural populations ( p = 0.027). Conclusion: Future interventions targeting rural and less well‐educated populations may improve care with the goal of increasing the span of healthy life and reducing survival disparities related to SNAC.